TEORI PENGETAHUAN IMMANUEL KANT DAN IMPLIKASINYA TERHADAP BATAS ILMU - Noor, Irfan (Jurnal Ilmiah Ilmu Ushuluddin, 2010)
In modern philosophy, the discourse on the border of knowledge has devel-oped, especially when positivism has become a dominant paradigm. Infact the roots of its epistemological problems can be found in ImmanuelKant?s theory of knowledge. Kant?s view of the conditions of possibility ofhuman mind eventually leads to a dogma that what can be investigated isonly the phenomena. This dogma has become the basis for positivism toestablish the knowledge border.